Clinical signs, lesions and viral antigen distribution in alpacas (Vicugna pacos) naturally infected with Rift Valley fever virus - Odendaal, Lieza (University of Pretoria, 2024)
Dissertation (MMedVet Pathology (Veterinary Science))--University of Pretoria, 2024.